Comparative Review of Cellulose Acetate, Polyacrylonitrile, and Polyvinyl Alcohol-Based Hydrophilic Membranes for Desalination - Romario Abdullah; Alvin Romadhoni Putra Hidayat; Novia Amalia Sholeha (Universitas Diponegoro, 2026)
The issue of clean water scarcity has become one of the most critical challenges threatening the global population today. It is estimated that approximately 6 billion people will experience water stress and shortages by 2050. One promising solution to address this challenge is the implementation of desalination technologies to convert seawater into freshwater. Among the available approaches, membrane-based desalination offers significant advantages, including lower energy requirements, cost-effective fabrication, and improved environmental sustainability. Polymeric membranes with high hydrophilicity have shown considerable potential for further development, particularly those based on cellulose acetate (CA), polyacrylonitrile (PAN), and polyvinyl alcohol (PVA), each exhibiting distinct advantages as materials for desalination applications. Key parameters influencing membrane performance include hydrophilicity, permeability, membrane thickness, pore size, and porosity. Based on the reviewed studies, membranes synthesized using PVA demonstrate superior characteristics in terms of permeability, optimal thickness, pore size, and porosity. These properties contribute to enhanced water flux and salt rejection performance compared to membranes fabricated from CA and PAN